2015
DOI: 10.1159/000370248
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Inhibition Improves Erectile Function in a Rat Model of Cavernous Nerve Injury

Abstract: Introduction: Erectile dysfunction (ED) after cavernous nerve (CN) injury remains difficult to treat. Calpain plays a critical role in causing neurodegenerative diseases. This study aimed to evaluate whether calpain inhibition preserves erectile function in a rat model of CN injury. Materials and Methods: Rats underwent sham surgery or CN crush injury. The CN-crushed rats were treated with vehicle or MDL-28170, a specific calpain inhibitor. At 1, 2, 3, and 7 days post-surgery, major pelvic ganglia (MPG) were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…A previous study showed that calpain inhibition by the calpain inhibitor MDL28170 could preserve the erectile response and neuronal nitric oxide synthase expression in rats suffering from cavernous nerve injury. 20 However, whether calpain inhibition can ameliorate diabetic ED has not yet been studied. In the present study, we used a diabetic model of mice induced with streptozotocin to investigate the effect of calpain inhibition on diabetic ED and explore the possible underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that calpain inhibition by the calpain inhibitor MDL28170 could preserve the erectile response and neuronal nitric oxide synthase expression in rats suffering from cavernous nerve injury. 20 However, whether calpain inhibition can ameliorate diabetic ED has not yet been studied. In the present study, we used a diabetic model of mice induced with streptozotocin to investigate the effect of calpain inhibition on diabetic ED and explore the possible underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Intracavernous pressure (ICP) and mean arterial blood pressure (MAP) were measured as previously described in our experiment 26. Electrostimulation of the cavernous nerve (CN) was applied as voltage response to stimulation (2.5 V, 5V, and 7.5 V) at 15 Hz with a pulse width of 0.5 ms for 50 s. Three stimulations were conducted at each side of the CN.…”
Section: Methodsmentioning
confidence: 99%
“…As described previously,2627 briefly, 40 μg of total protein was transferred onto a nitrocellulose membrane (Pierce, Rocford, IL, USA) and incubated with appropriate dilutions of the primary specific antibody, including anti-Akt, anti-phospho-Akt (Thr308), anti-phospho-Akt (Ser473), anti-eNOS, anti-phospho-eNOS (Thr495), anti-phospho-eNOS (Ser1177) (1:1000, CST, Danvers, MA, USA), anti-GRK2, anti-gp91 phox , anti-caspase-3, anti-active (cleaved) caspase-3 antibody (1:1000, Abcam, Cambridge, MA, USA), followed by incubation with horseradish peroxidase (HRP) conjugated secondary antibody. The membranes were then analyzed using a chemiluminescence detection system.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, minimizing oxidative stress can be a feasible approach to CN recovery. Also, it was found that calpain, a calcium‐dependent, non‐lysosomal neutral cysteine endopeptidase, and its activation have a role in the pathogenesis of CNI related ED 33 . Calpain inhibition improved erectile responses and neuronal NOS (nNOS) expression with a decrease in TGF‐β1 and collagen expression in penile tissue from CNI rats 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was found that calpain, a calcium‐dependent, non‐lysosomal neutral cysteine endopeptidase, and its activation have a role in the pathogenesis of CNI related ED 33 . Calpain inhibition improved erectile responses and neuronal NOS (nNOS) expression with a decrease in TGF‐β1 and collagen expression in penile tissue from CNI rats 33 . The inhibition of calpain could be a choice among the new approaches to prevent the development of ED after CNI 33 .…”
Section: Introductionmentioning
confidence: 99%